The Effect Of Board Capital On The Efficiency Of Indonesian Commercial Banks In 2020-2022 - Steven Sanjaya; Luky Patricia Widianingsih (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to examine whether Board Capital factors have an effect on the efficiency of state-owned and private commercial banks in Indonesia. This study uses secondary data from annual reports and LinkedIn for 48 commercial banks in Indonesia for the period 2020-2022. The results of the study show that Education Capital does not have an effect on bank efficiency, Experience Capital has a negative effect, and Networking Capital has a positive effect. The significant control variables are NIM, Bank size, Bank age, and Pandemic year. Board of directors' networking becomes an important factor in improving bank efficiency in Indonesia.